Forced adaptations of sporting behaviours during the Covid-19 pandemic and their effects on subjective well-being - Mutz, M. (European Societies, 2020)
Few studies have shown that exercise withdrawal and forced inactivity lead to negative mood states and increased symptoms of depression. Involuntary inactivity has become reality for millions during the Covid-19 pandemic, as mitigation and containment policies included the closings of sports facilities and leisure infrastructures. Based on representative survey data from Germany (=14 years, N=1001), the paper addresses the changes in sport and exercise activities in the pandemic situation and their association with emotional well-being. Findings show a reduced level of emotional well-being in the German population during the Covid-19 pandemic. In particular, those individuals who stopped or considerably reduced their sport and exercise activities during the pandemic report a significant decline of well-being compared to the time before the pandemic. Individuals, who reduced sport and exercise due to external constraints, reported the largest decline in well-being. In contrast, the small group of individuals who intensified their sporting activities during the pandemic stands out with the most positive well-being levels. Irrespective of sport and exercise adaptations, findings additionally show that females report a steeper decline in well-being during the crisis compared to men.